Boosting the Donor Effect of Side‐On W(II) Alkyne Complex Based Diphosphines. Issue 36 (18th November 2022) - Thiem, Paula; Ludwig, Stephan; Villinger, Alexander; Seidel, Wolfram W.
Abstract: Redox‐active tungsten alkyne complex‐based phosphines of the type [Tp*W(CO)Br(η 2 ‐C2 (PR2 )x ] (x=1, 2; R=Ph, i ‐Pr) and coordination experiments with the corresponding diphosphines are described. The p K B values of the terminal free phosphine groups were estimated indirectly by the 1 J P/Se coupling constants in the associated P‐selenides. A ten orders of magnitude higher basicity for the bis(diisopropyl)phosphine derivatives compared to the diphenyl congener as well as a significant difference in basicity of the phosphine depending on its position at the alkyne was determined. The diphosphines were utilized for comparative coordination experiments with Ni(II) and Cu(I) as first row transition metals. The heterobimetallic complexes {[Tp*W(CO)Br(μ‐η 2 ‐ C, C′ ‐κ 2 ‐ P, P′ ‐C2 (PR2 )2 ]NiCl2 } (R=Ph, i ‐Pr) were synthesized and fully characterized, the large difference in basicity and donor strength being underlined by a different degree of stability. Furthermore, two Cu(I) complexes of the isopropyl diphosphine derivative are presented and discussed; one of both being a dinuclear phenanthroline Cu(I) complex and the other a tetranuclear complex exhibiting an angled Cu2 Br + core. Abstract : The donor strength of redox‐active alkyne based diphosphine ligands is substantially improved, as determined by NMR studies with the corresponding P‐selenides. The metalla‐diphosphines could then be employed to form a series of heterobimetallic complexes of Ni(II) and Cu(I) as examples of the first transition metal row.